Calcific Discitis Seems to be a Common Incidental Finding in Adults - Gossner, Johannes (Indian Journal of Radiology and Imaging, 2022)
Calcific discitis seems to be a rare cause of back pain in adults. Imaging shows a calcification of the nucleus pulposus with extension through the endplates on computed tomography. This can be accompanied by bone marrow edema on magnetic resonance imaging. In a retrospective review of 150 patients, 4 cases of calcific discitis were found (2.8%). None of the patients reported about back pain. Therefore, it seems that symptomatic cases of calcific discitis are a rare occurrence in contrast to the quite frequent incidental finding of asymptomatic cases on imaging. Knowledge of the various imaging appearances of calcific discitis is necessary for radiologists, because especially in acute cases with substantial bone marrow edema, this benign entity may be confused with infectious spondylodiscitis or malignancy.
Keywords: spinal imaging; calcific discitis; prevalence; incidental finding